2023
DOI: 10.7759/cureus.36814
|View full text |Cite
|
Sign up to set email alerts
|

The Clot Thickens: COVID-19-Related ST-Elevation Myocardial Infarction in the Setting of Recent Boosters

Abstract: The coronavirus disease of 2019 has an array of pathological effects that continue to be discovered. Vaccines against COVID-19 have quickly emerged as our main tool. However, the thrombotic risk of both the virus and the vaccine is yet to be established, let alone together. In this case report, we present a case involving a recently diagnosed COVID-19 patient who developed an ST-elevated myocardial infarction (STEMI) after receiving his booster shot. Our aim is to highlight the standard of treatment outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…While the correlation between these infrequent events and vaccination remains uncertain, their manifestation post-vaccination in healthy individuals without other apparent causes could suggest a potential association [67]. Potential mechanisms contributing to MI post-vaccination encompass Kounis syndrome inducing MI through allergic vasospasm or stent occlusion infiltrated by eosinophils or mast cells; vaccine-induced thrombotic thrombocytopenia characterized by abnormal blood clot formation and low platelet levels; ACS following influenza vaccine administration due to shared excipients like polysorbate 80 with COVID-19 vaccines; demand-supply mismatch ischemia triggered by vaccination-related stress, especially in elderly individuals with comorbidities; and myocarditis that can rarely occur post-vaccination, potentially leading to MI [68][69][70]. It has been observed that MI following the administration of COVID-19 vaccination occurred most frequently in males with a mean age of 63.45 years [69].…”
Section: Effect Of Covid-19 Vaccination On Stemimentioning
confidence: 99%
“…While the correlation between these infrequent events and vaccination remains uncertain, their manifestation post-vaccination in healthy individuals without other apparent causes could suggest a potential association [67]. Potential mechanisms contributing to MI post-vaccination encompass Kounis syndrome inducing MI through allergic vasospasm or stent occlusion infiltrated by eosinophils or mast cells; vaccine-induced thrombotic thrombocytopenia characterized by abnormal blood clot formation and low platelet levels; ACS following influenza vaccine administration due to shared excipients like polysorbate 80 with COVID-19 vaccines; demand-supply mismatch ischemia triggered by vaccination-related stress, especially in elderly individuals with comorbidities; and myocarditis that can rarely occur post-vaccination, potentially leading to MI [68][69][70]. It has been observed that MI following the administration of COVID-19 vaccination occurred most frequently in males with a mean age of 63.45 years [69].…”
Section: Effect Of Covid-19 Vaccination On Stemimentioning
confidence: 99%